Oral delivery of allopurinol niosomes in treatment of gout in animal model. (3rd April 2017) - Singh, Neelu; Parashar, Poonam; Tripathi, Chandra Bhushan; Kanoujia, Jovita; Kaithwas, Gaurav; Saraf, Shubhini A.
Abstract: Context : Gout is a painful disorder which does not have an efficient delivery system for its treatment. Objective : Development and in vitro, in vivo evaluation of allopurinol-loaded nonionic surfactant-based niosomes was envisaged. Materials and methods : Niosomes were prepared with Span 20 and Tween 20 (1:1 molar ratio) using ether injection method. The formulations were screened for entrapment efficiency, particle size analysis, zeta potential, release kinetics, in vivo activity, and stability studies. Result : Stable, spherical vesicles of average particle size 304 nm with zeta-potential and entrapment efficiency of 22.2 mV and 79.44 ± 0.02%, respectively, were produced. In vitro release study revealed 82.16 ± 0.04% release of allopurinol within 24 h. The niosomal formulation was further evaluated for its antigout potential in monosodium urate (MSU) crystal induced gout animal model. The formulation demonstrated significant uric acid level reduction and enhanced antigout activity when compared with the pure allopurinol. Discussion : The better antigout activity displayed by niosomal formulation could be attributed to sustained release of drug, higher drug solubility within biological fluids, better membrane interaction, smaller size, and presence of cholesterol and surfactant. Conclusions : This study reveals that niosomes can be an efficient delivery system for the treatment of gout.